Healthy Body, Healthy Mind: A Mindset Intervention for Obese Youth. Issue 6 (1st November 2020) - Orvidas, K.; Burnette, J. L.; Schleider, J. L.; Skelton, J. A.; Moses, M.; Dunsmore, J. C.
Abstract: As growth mindset intervention research continues to develop, more work is needed to understand how to most effectively implement these interventions to encourage healthy cognitions and behaviors. The present study details the initial testing of a single-session, online mindset intervention ( Healthy Body, Healthy Mind ) for obese children and adolescents enrolled in obesity treatment clinics. Using a pre to post-test design, results indicated that growth mindsets of health and cognitions related to health behavior (nutrition and exercise self-efficacy and perceived control) increased significantly. However, despite efforts to mitigate feelings of culpability, blame also increased from pretest to post-test. Yet, body dissatisfaction decreased significantly. Intrinsic value for health behaviors remained unchanged from pretest to post-test. Analysis of narratives suggests that youth were engaged with the intervention content. Additionally, when youth's narratives incorporated themes related to the changeable nature of the attribute, they also self-reported stronger growth mindsets. In the discussion, we note implications of findings for the development of large-scale health-based growth mindset interventions that are developmentally-appropriate for children and adolescents.